The Role of Firm Age Moderation on The Effect of Profitability and Leverage on The Share Price of Pharmaceutical Companies Listed on The Indonesia Stock Exchange - Dwi Utami; Elwisam Elwisam; Kumba Digdowiseiso (Syntax Corporation Indonesia, 2023)
This study aims to analyze the role of firm age moderation on the effect of profitability and leverage on the share price of pharmaceutical companies listed on the Indonesia Stock Exchange. This research comes from secondary data obtained from the Annual Report of companies engaged in the pharmaceutical financial industry listed on the Indonesia Stock Exchange during the observation year, namely 2018-2022 through the IDX website (www.id.co.id). Descriptive Analysis and Moderation Regression Analysis are data analysis techniques used in this study with the EVIEWS 9 program. Based on the results of this study, it was found that Profitability has a positive and significant effect on stock prices and Leverage has a positive and significant effect on stock prices. As well as the age of the company is able to moderate the effect of profitability and leverage on the stock price.